Incidencia de cisticercosis porcina en cerdos que se faena en el camal del cantón Echeandía provincia Bolívar - Rea Milán, Rosa Inés (2025)
The present study aimed to determine the incidence of porcine cysticercosis in pigs slaughtered at the slaughterhouse in the Echeandía canton, Bolívar Province. Porcine cysticercosis, caused by the larvae of Taenia soluim, is a zoonotic disease with a great impact on public health and a significant socioeconomic impact. During the study period, the samples analyzed were 100 slaughtered pigs, macroscopically examining organs and tissues affected by cysticercosis, such as the masseter muscles, intercostal muscles, femoral muscles, tongue, heart and liver. The results revealed the total absence of positive cases of cysticercosis, reflecting a 0% incidence for all the variables proposed in the study, such as sex, breed, origin and age. It is worth highlighting the appropriate control carried out at the slaughterhouse, the implemented traceability and production quality. In conclusion, no cysticercosis was detected at the Echandia slaughterhouse during the study period. It is essential to maintain and reinforce sanitary and hygiene control measures at the slaughterhouse, as this will allow for continuous monitoring of cysticercosis, ensuring food safety and public health in the Canton.